2022
DOI: 10.1002/anie.202211674
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Based Metal–Organic Nanoradiosensitizers Enhance Radiotherapy by Combining ROS Generation and CO Gas Release

Abstract: A lack of targeting accuracy and radiosensitivity severely limits clinical radiotherapy. In this study, we developed a radiosensitizer comprised of Ru-based metal-organic nanostructures (ZrRuMn-MONs@mem) to optimize irradiation by maximizing reactive oxygen species (ROS) generation and CO release in X-rayinduced dynamic therapy (XDT). The well-designed nanostructures increase the direct absorption of radiation doses (primary radiation) and promote the deposition of photons and electrons (secondary radiation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…As shown in Figure j, we further assessed the intracellular ROS production in 4T1 cells using a 2′,7′-dichlorofluorescin diacetates (DCFH-DA). , From the results, the Zn-Car MNs treated group showed a higher green fluorescence than the Zn 2+ treated group, suggesting that Zn-Car MNs produced more ROS within cancer cells.…”
Section: Anticancer Efficacy In Vitromentioning
confidence: 99%
“…As shown in Figure j, we further assessed the intracellular ROS production in 4T1 cells using a 2′,7′-dichlorofluorescin diacetates (DCFH-DA). , From the results, the Zn-Car MNs treated group showed a higher green fluorescence than the Zn 2+ treated group, suggesting that Zn-Car MNs produced more ROS within cancer cells.…”
Section: Anticancer Efficacy In Vitromentioning
confidence: 99%
“…Dai et al. ( 43 ) developed a ruthenium-based metal-organic nanostructured radiotherapy sensitizer (ZrRuMn-MONs@mem) for the combined treatment of ROS and CO by increasing the direct absorption of radiation dose and facilitating the deposition of photons and electrons. In the present study, ruthenium metal-organic nanostructures show unique advantages in radiotherapy sensitization.…”
Section: Categories Of Nanomaterials Applied In Radiotherapymentioning
confidence: 99%
“…The X-ray-triggered generation of ˙OH and CO release from the nanoparticles were independent of oxygen, which induced remarkable therapeutic efficacy against both normoxic and hypoxic cancers. In another example, Liu et al 49 reported ZrRnMn-based metal–organic nanostructures for the combination of radiotherapy and gas therapy by maximizing the generation of reactive oxygen species (ROS) and CO release under X-ray radiation. Inside the nanoparticles, the Zr cluster absorbed X-rays, and Ru(bpy) 2 was activated for the production of ROS.…”
Section: X-ray-triggered Gas Releasementioning
confidence: 99%